Ginsenoside Rg1 Attenuates Muscle Atrophy in Hyperglycemic Conditions, Inactivity and Protein Deprivation Models via AKT/mTOR Pathway Activation - He, Xu; Li, Yan; Chen, Jun; Zhang, Li; Huang, Yan; Zhou, Ying; Li, Jing (Current Molecular Medicine, 2025)
<span class=
Keywords: AKT/mTOR Pathway